2012
DOI: 10.4103/2231-0738.95936
|View full text |Cite
|
Sign up to set email alerts
|

Anti-edematogenic and analgesic activities of Ficus benghalensis

Abstract: This work was done for the investigations of anti-inflammatory and analgesic activities of methanolic extract of dried leaves of Ficus benghalensis Linn. by oral administration at doses of 10, 20 and 100 mg/kg of body weight to healthy animals. The extract was studied for anti-inflammatory activity by using carrageenan-induced hind paw edema in rats. The mean increases in paw volume and % inhibition in the edema were measured plethysmometrically at different time intervals after carrageenan (1% w/v) injection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Most past studies have, however, shown that different plant-parts, namely bark[ 9 ] and leaves[ 3 9 ] did have analgesic and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most past studies have, however, shown that different plant-parts, namely bark[ 9 ] and leaves[ 3 9 ] did have analgesic and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In allopathy, pharmacological screening of plants often provides basis for developing new lead molecules. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in allopathy, pharmacological screening of plants often provide basis for developing new lead molecules [1, 2]. The recent advancements in phyto-chemistry and molecular biology have renewed and rejuvenated our interest in herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many attempts to prove analgesic and anti-inflammatory [2, 13], antistress and antiallergic [14], antimicrobial [15, 16], antiplasmodial [17], mosquito larvicidal [18] anti-ulcer [19], antifungal [20], anti-lipidemic [21] anti-atherogenic [22] antidiabetic [23, 24] properties of various parts of the plant. Though mainstream medicine has claimed several interesting findings, no break-through has yet been achieved [25].…”
Section: Introductionmentioning
confidence: 99%